Effects of insulin and lipid emulsion on renal haemodynamics and renal sodium handling in IDDM patients - Pelikánová, T; Smrcková, I; Krízová, J; Stríbrná, J; Lánská, V (Diabetologia, 1996)
To evaluate the role of insulin and hypertriglyceridaemia in the regulation of renal haemodynamics and sodium handling in insulin-dependent diabetes mellitus (IDDM), 11 IDDM patients without microalbuminuria and 13 weight-, age-, protein intake- and sex-matched healthy control subjects were studied. Clearances of inulin (Cin), para-amino-hippuric acid (CPAH), sodium (CNa), and lithium (CLi) were measured in four 60-min clearance periods (periods I, II, III and IV) during isoinsulinaemia with lipid emulsion infusion (study 1), a hyperinsulinaemic isoglycaemic clamp with Intralipid infusion (study 2), and during time-controlled isoinsulinaemia (study 3). We found that Cin, CPAH and filtration fraction were comparable in IDDM and control subjects, whereas CNa was decreased in diabetic subjects (2.01 +/- 1.11 vs 3.03 +/- 1.32 ml/min; p < 0.05) due to elevations of proximal tubular fractional and absolute reabsorptions of sodium (p < 0.05). Insulin infusion did not affect Cin, increased CPAH (p < 0.05) and, consequently, lowered the filtration fraction (p < 0.01) in both groups. While acute hyperinsulinaemia resulted in increases in distal tubular fractional and absolute reabsorptions of sodium (p < 0.01) contributing to a fall in CNa (p < 0.01) in control subjects, in diabetic subjects the sodium-retaining effect of insulin was not significant. The lipid emulsion did not alter any of the estimated parameters. We conclude that IDDM without microalbuminuria is associated with a tendency to sodium retention which is not aggravated by insulin when compared to control subjects. Acutely induced hypertriglyceridaemia does not alter renal haemodynamics or renal sodium handling.
Keywords: dospělí; Kidney; Inulin; Sodium; Female; intravenózní infuze; Kidney Tubules; Fat Emulsions, Intravenous; Adult; metabolická clearance; lithium; ženské pohlaví; kyselina p-aminohippurová; Glomerular Filtration Rate; triglyceridy; Hemodynamics; tukové emulze intravenózní; hemodynamika; Lithium; Fatty Acids, Nonesterified; Triglycerides; lidé; Blood Glucose; renální oběh; glykemický clamp; referenční hodnoty; ledvinové kanálky; Glycated Hemoglobin A; Diabetes Mellitus, Type 1; Male; inulin; sodík; Metabolic Clearance Rate; Reference Values; Renal Circulation; Infusions, Intravenous; kyseliny mastné neesterifikované; glykovaný hemoglobin; p-Aminohippuric Acid; mužské pohlaví; Glucose Clamp Technique; ledviny; krevní glukóza; Glycated Hemoglobin; diabetes mellitus 1. typu; hodnoty glomerulární filtrace; Humans